Nursing Care Considerations in Submandibular Salivary Gland Excision - Alotaibi, Maryam Shaker Ojayr; Reem Mohammed Ali Moafa; Abdulaziz Jassim Alshehabi; Mariam Kalaf Alenaze; Arwa Ahmad Fallatah; Abdulrahman Muhammad Alsharifi; Khadijah Mohammed Hanashi; Ahmed Abdrabalameer Alrashid; Nourah Shabak Naga Al Dhafeeri; Abdulmohsen Olayan Alenazi; Ali mohammed Ibrahim Abu Jamilah; Khaled Hussein Abdullah AlSudairi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The submandibular salivary glands play a vital role in baseline saliva production, and their dysfunction commonly leads to obstructive and inflammatory conditions requiring surgical intervention. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to comprehensively review nursing care considerations associated with submandibular salivary gland excision, emphasizing anatomy, indications, surgical technique, complications, and interprofessional care. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative educational review was conducted, synthesizing current anatomical, physiological, and clinical knowledge related to submandibular gland excision, with particular focus on perioperative nursing responsibilities. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Recurrent sialolithiasis, chronic sialadenitis, neoplasms, and refractory sialorrhea were identified as primary indications for excision. Surgical success depends on meticulous technique and preservation of critical neurovascular structures. Postoperative nursing monitoring is essential for early detection of complications such as hematoma, infection, and nerve injury. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective nursing assessment and interprofessional collaboration significantly enhance patient safety, functional recovery, and overall outcomes following submandibular gland excision.